1954
DOI: 10.1042/bj0580038
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of carbohydrates in retinal extracts

Abstract: I954 fellowship. He wishes to express his gratitude to the Fund for its generous support, and to Prof. J. W. Williams for his courteous hospitality and for the facilities which he made available during the tenure of the fellowship. The help of Dr C. S. Hanes and Dr A. G. Ogston in the preparation of the manuscript is gratefully acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1958
1958
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Normal rats (140-240 grams) and rabbits (2)(3)(4)(5) in the fed state were utilized. Dog eyes were obtained from animals used in other experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal rats (140-240 grams) and rabbits (2)(3)(4)(5) in the fed state were utilized. Dog eyes were obtained from animals used in other experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Also, he showed that retinal glycolytic activity even exceeded that of many tumors. It has since been indicated (2,3) that the breakdown of glucose to pyruvic acid in the retina is accomplished through the Embden-Meyerhof pathway, and that the citric acid cycle is probably a further step in its degradation (4). As late as 1961 Rahman and Kerly ( 5 ) concluded, from studies with specifically labelled glucose (214, that the Hexose Monophosphate shunt was responsible for about 25 O / o of retinal glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…He appended a list of works by current rectors and professors which were on display in churches, convents, and imperial palaces, as well as private houses, emphasizing their dissemination in the public as well as the private sphere. 98 There were other ways, too, that Russians began to fl ex their muscles in artistic discourse at the turn of the century. The fi rst Russian journal devoted to the visual arts appeared in 1807 (even if published by a Frenchman and written in French), and Russian scholars began to write practical and theoretical treatises on the fi ne arts, among them Petr Chekalevskii's Discourse on the Free Arts (1792), which included excerpts from Winckelmann's texts.…”
mentioning
confidence: 99%
“…This pair of reactions would yield the stoichiometry suggested by Meyer hof. Hexokinase alone catalyzes the following reaction: Hexokinase has been found in yeast (McDonald, 1955); bacteria (Crane, 1962); locust muscle (Kerly and Leaback, 1957a); intestine, kidney, and heart (Cori, 1945); brain (Sols and Crane, 1954;Kerly and Leaback, 1957b;Schwartz and Basford, 1967); liver and skeletal muscle (Crane and Sols, 1955); and other tissues (Long, 1952;Hoare and Kerly, 1954). Enzymes of this type appear to be ubiquitous in nature and probably all cells capable of metabolizing hexoses contain at least one such enzyme (Crane, 1962).…”
Section: General Introductionmentioning
confidence: 99%